Development Implementation Traditional Market in the Kuningan District - Anwar (Decision, 2023)
Traditional markets are meeting locations for merchants and buyers, with direct seller-buyer interactions and, in most cases, a bargaining process. People will be quite satisfied with the existence of traditional marketplaces because they give many essential and daily commodities at lower prices. As a result, traditional markets must be developed more effectively. To improve tourist attention, adjustments or innovations are required. Traditional markets in Kuningan Regency are being developed in a variety of ways, including physical renovation, revitalization of traditional markets, market cleanliness and market environment activities, arrangement of places and grouping of types of merchandise, orderly administration, order, and security. The Traditional Market Development Policy is based on Kuningan Regency's Regional Regulation (PERDA) Number 11 of 2011, which governs the arrangement and development of shopping centers. Traditional Markets and Modern Shops (Kuningan Regency Government Office). Meanwhile, supportive variables include merchants who always follow market managers' instructions, the availability of cleaning workers, and positive backing from the Department of Industry and Trade. The goal of this research is to investigate and seek theoretical explanations to policy network principles, as well as to develop new policy network concepts. This research employs qualitative descriptive methodology and data collection approaches.